Pre- and post-operative voice therapy for benign vocal fold lesions: protocol for a non-randomised, multicentre feasibility trial with embedded process evaluation - Anna White; Paul Carding; Vicky Booth; Julian McGlashan; Jarrad Van Stan; Pip Logan; Rehab Awad (Pilot and Feasibility Studies, 2024)
Abstract Background Management of benign vocal fold lesions (BVFLs) is variable with individuals receiving surgery, voice therapy, or a combination of these approaches. Some evidence suggests that the best outcomes may be achieved when patients are offered pre- and post-operative voice therapy in addition to phonosurgery, but what constitutes pre- and post-operative voice therapy is poorly described. The pre- and post-operative voice therapy (PAPOV) intervention has been developed and described according to the TIDieR checklist and Rehabilitation Treatment Specification System (RTSS) for voice. The PAPOV intervention is delivered by specialist speech and language therapists trained in the intervention and comprises 7 essential and 4 additional components, delivered in voice therapy sessions with patients who are having surgery on their vocal folds for removal of BVFLs. Study design Non-randomised, multicentre feasibility trial with embedded process evaluation. Method Forty patients from two sites who are due to undergo phonosurgery will be recruited to receive the PAPOV intervention. Measures of feasibility, including recruitment, retention, and adherence, will be assessed. The feasibility of gathering clinical and cost effectiveness data will be measured pre-treatment, then at 3 and 6 months post-operatively. An embedded process evaluation will be undertaken to explain feasibility findings. Discussion This study will assess the feasibility of delivering a described voice therapy intervention protocol to patients who are undergoing surgery for removal of BVFLs. Findings will be used to inform the development and implementation of a subsequent effectiveness trial, should this be feasible. Trial registration This trial has been prospectively registered on ISRCTN (date 4th January 2023), registration number 17438192, and can be viewed here: https://www.isrctn.com/ISRCTN17438192 .